Lifestyle Alterations During the COVID-19 Pandemic and Its Impact on Obesity amongst Indonesian University Students - Nur Jannah Binti Azhar; Zettira Dwi Zahra; Dina Anandita Irawan; Sofa Rahmannia (Sriwijaya Journal of Medicine, 2022)
Covid-19 pandemic caused large-scale mobility restrictions, including for students. This condition might induce lifestyle changes which could impact metabolic conditions. This study aims to (1) investigate lifestyles pre and mid pandemic; (2) investigate the relative differences of the students' BMI early pandemic until recent; (3) estimate the relationship between lifestyle alterations and increased BMI during the pandemic. The research conduct using an online survey of 110 students spread across Indonesia in the first to ninth semesters. Analysis was performed using the Wilcoxon signed-rank test and Spearman's analysis. The results showed that there were lifestyle alterations; namely, 15% of respondents reduced their walking habits, duration, and the number of steps. 9% reduced exercise frequency, with more than 50% of respondents reducing their exercise duration. Nearly 20% increased sedentary frequency. 11% experience stress and take it out on food. As many as 93% of respondents maintain the habit of consuming sweet drinks. Moreover, 66% experienced increased BMI during the pandemic, with almost 30% changing nutritional status from normal to overweight or obese. The median BMI increased by 0.5 kg/m2 with a significant difference (p=0.001). Finally, of all lifestyle alterations during the pandemic, two lifestyles had a significant effect on the increase in BMI, namely changes in the frequency of exercise (p=0.03) and consumption habits of sugary drinks (p=0.05). In conclusion, lifestyle changes in students during the pandemic occurred and impacted the increase in BMI. Priority of intervention should be made in this population to prevent a further increase in obesity in Indonesia.